Local Extremums of Trigonometric Polynomial - Belov, I. S. (Журнал математичної фізики, аналізу, геометрії, 2007)
Local extremes of the trigonometric polynomial $B_n(θ)=\displaystyle\sum_{k=n}^{k=2n}\displaystyle\frac{\sin kθ}{k}$ are considered, and various inequalities between them are proved. In particular, the greatest and the least values of $B_n(θ)$ are found. Mathematics Subject Classification: 26A09.